A “malignant” cause for syncope: Cardiac metastases from tonsillar carcinoma - A.J. Ashwal; Padmakumar Ramachandra; Krishnananda Nayak; Mukund A. Prabhu; Vidya Monappa (IHJ Cardiovascular Case Reports, 2018)
We report a rare case of a 64-year-old patient with recurrent syncope and a history of tonsillar carcinoma under treatment for the past three months. ECG showed complete heart block and echocardiography revealed cardiac metastases at atrioventricular junction. This case report highlights the fact that sometimes unusual causes can be responsible for syncope such as cardiac metastases in this patient resulting in complete heart block. This implies the need for screening for cardiac metastases in all patients with malignancies who present with syncope.